Association of occupational burnout and sociodemographic data in nurses - Santes Bastián, María del Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Objective: to analyze the association of occupational burnout and sociodemographic data in nursing professionals from a second level of care hospital in Mexico. Method: Analytical, cross-sectional study, population of 78 nursing professionals, the 30-item Occupational Burnout Scale (EDO) was used. Descriptive and inferential statistics were obtained, such as frequencies, percentages and Pearson's Chi2. Results: An association was found between occupational burnout and academic training (p=.018), absences from work (p=.047) and gender (p=.947). Conclusions: A minimal part of the population presents occupational burnout at work.